Some Algorithms for the Error Linear Complexity of Binary 2^n-Periodic Sequences - Chang, Zuling; Wang, Xueyuan; Duan, Li (Wuhan University journal of natural sciences, 2013)
Based on the Games-Chan algorithm and StampMartin algorithm, this paper provides some new algorithms to compute the error linear complexity spectrum of binary 2n-periodic se- quences. These new algorithms are clearer and simpler than old algorithms, and they can quickly compute the error linear com- plexity spectrum of sequences according to different situations. We also discuss such algorithms and give some new results about linear complexity and error linear complexity of sequences.